Business Lawyer and the Rule of Law in Brazil (1990-2000) - Engelmann, Fabiano (Política. Revista de Ciencia Política, 2011)
The present text seeks to analyze the sphere of business law in Brazil lawyers space and its relation to judicial reform in the context of the internationalization of Brazilian law. Utilizing a “law & economics” approach, the paper profiles major law firms and their partners and the proliferation of arbitration courts. The empirical research relies on the qualitative study of documents and interviews carried out with jurists and political leader, with a goal towards understanding the relation between the international circulation of lawyers and the importexport of institutional models, as well as their its repercussions for the redefinition of the legal and political space in Brazil.